Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1073/pnas.1517094113
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sources of variation in language acquisition

Abstract: A fundamental question in the study of human language acquisition centers around apportioning explanatory force between the experience of the learner and the core knowledge that allows learners to represent that experience. We provide a previously unidentified kind of data identifying children's contribution to language acquisition. We identify one aspect of grammar that varies unpredictably across a population of speakers of what is ostensibly a single language. We further demonstrate that the grammatical kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
(40 reference statements)
0
19
0
Order By: Relevance
“…Children receive restricted input both quantitatively (in terms of the number of utterances they are exposed to) and qualitatively (in terms of how well the data point to the structures to be acquired). More than 50 years later, debates over the innateness of specific linguistic devices still turn on arguments based on poverty of the stimulus (for a current discussion, see Han et al 2016, Piantadosi & Kidd 2016). Developmental arguments that hinge on the input extend far beyond the problem of language acquisition.…”
Section: Statistics Of What? the Primitives Over Which Statistics mentioning
confidence: 99%
See 1 more Smart Citation
“…Children receive restricted input both quantitatively (in terms of the number of utterances they are exposed to) and qualitatively (in terms of how well the data point to the structures to be acquired). More than 50 years later, debates over the innateness of specific linguistic devices still turn on arguments based on poverty of the stimulus (for a current discussion, see Han et al 2016, Piantadosi & Kidd 2016). Developmental arguments that hinge on the input extend far beyond the problem of language acquisition.…”
Section: Statistics Of What? the Primitives Over Which Statistics mentioning
confidence: 99%
“…Statistical learning accounts are not sophisticated enough to be able to account for many detailed aspects of language acquisition, especially some of the more complex linguistic structures that do not appear to be transparently mirrored in the input (e.g., Han et al 2016). However, both experimental tasks and computational models have suggested specific ways in which constraints on statistical learning might have influenced the structure of natural languages (e.g., Christiansen & Chater 2008, Saffran 2001b, Smith et al 2017).…”
Section: Why Are We Statistical Learners?mentioning
confidence: 99%
“…Moreover, this variability was not simply due to the difficulty of computing interpretations; when the universal was in subject position, all speakers allowed only the interpretation where the universal takes wide scope. Finally Han, Musolino and Lidz (2016) found that speakers were consistent in their judgments across multiple testing sessions, and that they were consistent in their scope assignments for both kinds of negation in Korean. This pattern supports the view that each speaker controls only one grammar, with the variability in scope judgments following from which grammar that is.…”
Section: Children's Scope and The Character Of Syntactic Learningmentioning
confidence: 78%
“…To explore this possibility further, Han, Musolino and Lidz (2016) tested a group of children with their parents. They found again that roughly half of both populations allowed the universal to scope over negation.…”
Section: Children's Scope and The Character Of Syntactic Learningmentioning
confidence: 99%
“…Each learner must observe the linguistic behavior of others, and use their endogenous abilities to discover a grammar that accounts for this input (Han et al, 2016). These abilities interject a bias towards certain analyses, and so subtle changes in the input can lead to novel patterns different from those used by the previous generation (Grünwald, 2007;Langley and Stromsten, 2000;Senghas and Coppola, 2001).…”
Section: How Grammatical Complexity Developsmentioning
confidence: 99%